Diagnostic study on the energetics aspects of hiatus in the advance of southwest monsoon - Dutta, Somenath; De, U. S.; Devi, Sunitha (Mausam, 2009)
Advance of southwest monsoon, after its onset, often gets stalled for a week or more causing concern to the farmers and other community whose activities are weather dependent. The present study on the energetics aspect of hiatus in the advance of southwest monsoon over India aims at understanding the dynamical reasons for this. Nine cases of hiatus of duration more than 10 days during 1982-2006 have been selected. For each hiatus case, different energy terms, their generation and conversion among different terms have been computed during the hiatus period and also during the pre-hiatus pentad over a limited region between 65 degrees E to 90 degrees E, 5 degrees N to 30 degrees N. These computations are based on NCEP 2.5 degrees x 2.5 degrees re-analysed daily composite data during different hiatus period and during corresponding pre-hiatus pentad. From this study it is found that : (i) In most of the cases there is a reduction in the generation of zonal available potential energy [G(A(Z))] during hiatus period compared to pre-hiatus pentad. (ii) Drop in the conversion from zonal available potential energy to zonal kinetic energy [C(A(Z), K(Z))] during hiatus period has been observed in most of the cases. (iii) In most of the cases there is a reduction in zonal kinetic energy (K(Z)) and in eddy kinetic energy (K(E)) during hiatus period compared to pre-hiatus pentad.
Keywords: Energetics; Hiatus